PENERAPAN MODEL PEMBELAJARAN BLENDED LEARNING BERBASIS PLATFORM ALEF EDUCATION PADA PEMBELAJARAN MATEMATIKA - Herawati Herawati (Universitas Samudra, 2022)
ABSTRACT In this century, the conventional learning process in the classroom has lost its appeal. This happens because some students believe that with the increasing availability of technology, the process can be carried out online (e-learning). In order to adapt to technological developments without having to abandon face-to-face learning, there must be a strategy for implementing learning, delivering teaching and the right quality of teaching, namely blended learning. Blended learning is a learning model that combines the advantages of face-to-face learning and e-learning. Through blended learning, interaction and communication between students and teachers can be run in two directions, to support blended learning it is necessary to have a supportive online media and one of the online media for mathematics learning is the alef platform from the Alef Education company based in Abu Dhabi, United Arab Emirates. This platform can be used by Indonesian students thanks to the Cooperation of the Ministry of Religion of the Republic of Indonesia with the government of the United Arab Emirates. The Alef platform can be combined with a blended learning model because it can be used face-to-face and also online (e-Learning). The purpose of writing this study article is to find out how to apply the blended learning model with the Alef Education platform. The method used is a descriptive method with studies that link studies from various literature. In the end, it is hoped that this study can be used in the development of mathematics learning.